RUMAH ADAT DULOHUPA SEBAGAI IDENTITAS VISUAL GORONTALO - Udilawaty, Siska; Lasena, Yulianti (Venustas, 2024)
The Dulohupa traditional house is one of the traditional houses in Gorontalo which has an interesting and historical meaning that needs to be revealed to introduce it as one of the visual identities of Gorontalo so that it is known among tourists and the migrant community. On the basis of this knowledge, this research seeks to reveal the extent to which the visual image of the Dulohupa traditional house is one of the visual identities of the city of Gorontalo. Traditional houses have many meanings and symbols that need to be preserved. By knowing the meanings and ornaments, it is hoped that they can build a visual identity and attract tourists. The type of research used is a descriptive qualitative approach. The data collection method used is literature study. The results of identifying the characteristics of the Dulohupa traditional house show that the Dulohupa traditional house is an embodiment of local cultural values ​​and distinctive architectural art.